MicroRNA–mRNA Regulatory Network Associated with Cognitive Impairment in Multiple Sclerosis - Bruna De Felice; Federica Farinella; Giuseppe Romano; Concetta Montanino; Simona Bonavita; Deborah Archetto; Elisabetta Maida; Simona Raimo; Giacomo Lus; Maria Cropano; Cinzia Coppola; Elisabetta Signoriello (Molecular Neurobiology, 2026)
Cognitive impairment (CI) is a frequent and disabling manifestation of multiple sclerosis (MS), yet its molecular underpinnings remain poorly understood. This study aimed to identify microRNA (miRNA) signatures and related gene expression changes associated with CI in MS. Forty-six people with MS underwent clinical, radiological, and cognitive assessment. Peripheral blood mononuclear cells were collected for miRNA profiling using the miRCURY LNA miRNA Focus PCR Panel and validated through RT-qPCR. Experimentally validated miRNA target genes were retrieved using miRWalk with miRTarBase filtering. Target networks were constructed in Cytoscape, followed by protein–protein interaction analysis using STRING and functional enrichment analysis with database for annotation, visualization, and integrated discovery (DAVID) ( https://davidbioinformatics.nih.gov/ ). Selected target genes were further evaluated by gene expression analysis. The results showed that three miRNAs (i.e., miR-146a-5p, miR-let-7a-5p, and miR-21-5p) were significantly dysregulated in patients with MS with CI compared to those with preserved cognition. Gene expression analysis identified differential regulations of IL-1B, IL-6, SLC16A10, and NEFL, supporting the involvement of inflammatory and neurodegenerative pathways. Correlation analyses indicated specific miRNA–mRNA relationships underlying these alterations. These findings suggest that the combined dysregulation of miR-146a-5p and miR-21-5p, together with their target genes, constitutes a molecular signature associated with CI in MS. This profile could contribute to the development of miRNA-based biomarkers for early detection and monitoring of cognitive dysfunction in MS.